Gender from Sociocultural Perspective - Harutyunyan, Gohar; Hovhannisyan, Margarit (Armenian Folia Anglistika, 2013)
The pre introduced by R. Lakoff back in 1975sent article attempts to reveal the relevance of the distinctive provisions in male and female speech to modern English and Armenian. Extracts from fiction have been used as data for the investigation. Unlike English, in Armenian authors have had an opportunity to carry out their practical research based on the analysis of the answers to the questions prepared in advance.